Patho-physiological evaluation of Duranta erecta for the treatment of urolithiasis - Agawane, S. B.; Gupta, V. S.; Kulkarni, Mahesh J.; Bhattacharya, A. K.; Koratkar, Santosh; Rao, Vankudoth Koteswara (Journal of Ayurveda and integrative medicine, 2018)
Background: Urolithiasis is the third common disorder of the urinary system affecting 10-15% of the general population. In recent years, search for new antilithiatic drugs from natural sources has assumed greater importance. Objectives: This study was performed to investigate the anti-urolithiatic activity of methanolic extract of Duranta erecta leaves by in vitro and in vivo analysis. Materials and methods: The study was designed to determine presence of phytochemicals in D. erecta, its yield in percentage, antioxidant activity against 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and anti-microbial property against few bacteria. In vitro analysis was carried out study anti-urolithiatic property of D. erecta by nucleation assay and synthetic urine assay for inhibition of calcium oxalate and calcium oxalate monohydrate crystals formation. An in vivo experiment was performed on Wistar rats for confirmation of anti-urolithiatic property of D. erecta in animal model. Results: D. erecta has the presence of primary and secondary metabolites like glycoside, saponins, sterols, flavonoids, phenols, tannins, alkaloids, carbohydrates and proteins. Methanolic extract of D. erecta gave a very good yield (60%). D. erecta proved its antioxidant potential by 93.51% inhibition of DPPH radical at a concentration of 1000 μg/mL where ascorbic showed 94.71% of DPPH radical at the same concentration. In vitro tests like nucleation assay and synthetic urine assay showed that D. erecta inhibits formation of calcium oxalate and calcium oxalate monohydrate crystals. It also showed the anti-microbial property by formation of zone of inhibition against few bacteria. An in vivo experiment on Wistar rat animal model confirmed the anti-urolithiatic property of D. erecta L. leaves extract. Conclusions: Based on the results, we reported that D. erecta may treat calcium oxalate crystal deposition in the kidney by preventing hyperoxaluria-induced peroxidative damage to the renal tubular membrane surface (lipid peroxidation). It has anti-microbial potential so it may also inhibit the secondary bacterial infection in kidney. Based on the data, it can be concluded that this herb can be used as a potential anti-urolithiasis agent for kidney stone removal.